System Communication in Management Conflict of Natural Resources Development in Maluku Province - Risyart Alberth Far Far (Tropical Small Island Agriculture Management, 2022)
Regional conflicts in natural resource management can be caused by the limitations of interested parties in accessing natural resources. This paper aims to provide an overview of the management of natural resource development conflicts through mediation, the actors in natural resource development and to build a communication system model to minimize conflicts. The study concluded that the communication system in managing natural resource development conflicts was done through a mediation process. Mediation facilitates the involvement of conflicting parties and seeks a solution that benefits both parties. The actor is one approach in the structural flow, acting as the state's first or leading actor. As the first actor, the state has two functions: an actor user and protector of natural resources and the environment. The second factor is the entrepreneur (corporate, including mining companies), both at the global and national levels. The third actor in society is the weakest party. This actor almost always understands the process of marginalization or vulnerability to various forms of environmental degradation. The development conflict management communication system aims to change the behaviour of conflicting parties to reduce and resolve conflicts through dialogue and a participatory process